KNOWLEDGE LEVEL ON PREGNANT WOMEN ABOUT DANGER SIGNS OF PREGNANCY IN THE NGRAMBE COMMUNITY HEALTH CENTER, NGAWI REGENCY - Wibowo, Muhammad Farhan; Alami, Eqiel Navadz Akthar; Hidayat, Agung Wahyu (Cahaya Ilmu Bangsa Institute, 2024)
Indonesia is a country with the highest Maternal Mortality Rate (MMR) in Southeast Asia. Ngawi Regency itself still had high maternal mortality rate that recorder six pregnant women died in 2023, so this is still a concern for the local Ngawi Regency Government. Knowledge is one of many factors that influences the occurrence of maternal mortality in Indonesia. This study is descriptive and aims to evaluating level of knowledge about danger sign in pregnancy on maternal in Ngrawe district, Ngawi. The data used were primary data obtained from pretest and posttest using a questionnaire. The results of pretest were in the sufficient category on 18 samples (45%), 5 samples (12.5%) in poor category, and 17 others samples (42 .5%) in good category. And the postetst showed good result that all samples were able to answer all research questionnaire questions with correct answers The conclusion of this study is that knowledge is main factor to improve good labour in maternal and decrease MMR.